Examining the Impact of Microcredit on Women Entrepreneurs in Non-Profit Organizations: : Emerging Market Context - Saha, Debashis; Jinia, Israt Jahan (The Jahangirnagar Review, 2025)
This study examines the impact of access to finance (microcredit) on the financial sustainability and empowerment of women entrepreneurs involved with non-profit organizations (NPOs) in Bangladesh. Using a mixed-method approach, the research combines quantitative regression analysis with qualitative data collected from 200 women entrepreneurs through surveys, interviews, and focus group discussions in Sirajganj, Jessore, and Rajshahi. A multiple linear regression model examines the influence of microcredit factors—such as loan amount, repayment period, interest rate, training programs, and frequency of access—on financial sustainability and empowerment outcomes. The findings indicate a moderate positive relationship between these factors and both financial sustainability (R² = 0.226) and empowerment (R² = 0.245). While microcredit contributes to increased financial security, business growth, and economic participation, challenges like high interest rates, limited financial literacy, and cultural barriers reduce its full potential. Hypothesis testing confirms the statistical significance of at least one independent variable in both models. The study suggests that NPOs should offer flexible loan terms, strengthen training programs, and partner with financial institutions to improve outcomes. Despite limitations such as self-reported data, the research offers valuable insights into financial inclusion strategies and emphasizes microcredit’s role in promoting gender equality and rural development in Bangladesh.